Consumer credit, debt and investment in Europe - Consumer Protection in Europe: Theory and Practice (Conference) (2009 : Leeds, England); Devenney, James; Kenny, Mel. (Cambridge : Cambridge University Press, 2012)
'This topical collection of essays emanates from the Consumer Protection in Europe: Theory and Practice duo colloquium in December 2009. That conference explored consumer protection in Europe and covered topics which are even more relevant today given the revisions to the proposed Consumer Rights Directive, the appointment of an Expert Group on a common frame of reference and the Green Paper on European Contract Law. It was organised within the work programme Credit and Debt: Protecting the Vulnerable in Europe - a project placing emphasis on vulnerability in financial transactions. This volume focuses on consumer protection in credit and investments in the context of unprecedented turmoil in those markets and EU harmonisation initiatives in the area. It explores key issues such as responsible lending, information disclosure, consumer confidence, the regulation of consumer investment services and the protection of bank depositors'--
Includes bibliographical references and index.
Keywords: Consumer protection -- Law and legislation -- European Union countries -- Congresses; Consumer credit -- Law and legislation -- European Union countries -- Congresses; Investments -- Law and legislation -- European Union countries -- Congresses